New Teaching Staff in Higher Education in China Learning Lecturing in Mathematics - Yu, Mao (HRD Journal, 2013)
This study describes how a College of Mathematics (CM) in one Chinese provincial university implements a system of staff development to help new teaching staff learn how to lecture, describes what those involved think of the system, and evaluates the implementation from an Human Resource Development / Professional Development (HRD/PD) perspective. Data were collected from a field-based study over almost three months, involving 10 one-on-one interviews and five observations with six participants, – two managers and two pairs of mentors and novices, – who were selected by purposive sampling. It was found that implementation of the staff development policies in the CM created a ‘system’ involving input, a seven-component process, output, and feedback. The system worked principally on the basis of well-known HRD/PD strategies – mentoring, coaching, and modeling in which an experienced staff member (mentor) helped a new teaching staff member (novice) learn how to lecture, mainly through mutual classroom observation and discussion. Although all participants had generally positive attitudes towards the system, from a Western HRD/PD perspective the system had a number of serious weaknesses, which are discussed in the article. Key words : New Teaching Staff, Learning to Lecture, Higher Education, Evaluation